A Management Project presented in part consideration for the degree of General Masters of Business Administration - GRANJA, JUAN (2018)
The following study analyses the disruption created in the Ecuadorian insurance market when the government introduced a new law that regulates the market and its practices. Through the literature of institutional analysis, the topic is introduced by gathering all previous relevant studies and describe studies that have been made in similar cases. Therefore, we understand the importance of deepened the knowledge and intend to collaborate on its development by providing a case of a South American country. In this case, the above-mentioned law and the previous events are described and analyse to illustrate how polemical it was for the actors involved. From when the law was only focus on the best interest of the customers and the benefits they have with this service, to when the disruption point was achieved by introducing a provision that would involve the participation of the private sector to the public healthcare system. This provision was taken by the private sector as a threat given the negative consequences that their predictions showed. Then, it is described the institutional work in the form of repair work that was performed by the private industry and how the state through other forms of work managed to enact the law. The dispute built and the arguments utilized are analysed and questioned to illustrate the role that each one of the actors have, how limited their contribution can be, and the legitimacy of the actors. Afterwards, through the methods of grounded theory it is identified the forms of work and the outcome of the dispute.